Literature Review Manfaat Curcumin Untuk Endometriosis - Mayang - Chyntaka (POLTEKKES KEMENKES MANADO, 2022)
Background: Endometriosis is a chronic gynecological disease that affects women during their life cycle. Another opinion says that endometriosis is a chronic inflammatory disease associated with the hormone estrogen. It is estimated that more than 80 million women and girls worldwide suffer from endometriosis. Endometriosis occurs because menstrual blood flows back through the tube into the renal cavity and then implants in the cervical cavity where the endometrioma and endometrial invasion contain high levels of aromatase. Endometriosis is an inflammatory disease that depends on estrogen levels, due to P450 aromatase and a deficiency of 17β- hydroxysteroiddehydrogenase type 2. 17β-hydrosisteroid dehydrogenase type 2 converts strong estrogen (estradiol) into a weak estrogen (estron) that is active, which is not found in the luteal phase of endometriosis tissue. Goal: to further study the treatment of endometriosis by utilizing curcumin as a therapy that works to inhibit endometriosis cells by reducing the production of estradiol (strong estrogen). Method: This study is a Literature Review, using research journals related to endometriosis. Result: Endometriosis therapy can be done surgically based on the diagnosis that has been made, but the recurrence rate is higher. A combination of surgery and medical therapy is needed to get better results. The most widely used medical treatment is Gonadotropin-Releasing Harmon (GnRH) agonist and oral contraceptives as well as curcumin which works to inhibit endometriosis cells by reducing estradiol production.